THE RELATIONSHIP BETWEEN LEVERAGE, FREE CASH FLOW, AND INVESTMENT CASH FLOW ON ACCOUNTING CONSERVATISM OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Maria Veronika Wea; Ni Made Dwi Ratnadi (Adisam Publisher, 2025)
Accounting conservatism is a prudence principle applied by corporate management in preparing financial statements. This study aims to empirically examine the relationship between leverage, free cash flow, and investment cash flow and accounting conservatism in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research population consists of manufacturing companies continuously listed on the IDX from 2021 to 2023. A saturated sampling method was employed, whereby the entire population was used as the research sample, resulting in a total of 188 companies. Data were analyzed using multiple linear regression analysis. The results indicate that leverage, free cash flow, and investment cash flow are associated with accounting conservatism. Leverage and free cash flow show a positive relationship, meaning that higher leverage and free cash flow are associated with more conservative financial reporting by management. In contrast, investment cash flow exhibits a negative relationship, indicating that an increase in investment cash flow is associated with a decrease in the level of accounting conservatism.